Natriuretic Peptides in Post-mortem Brain Tissue and Cerebrospinal Fluid of Non-demented Humans and Alzheimer’s Disease Patients - Mahinrad, Simin; Bulk, Marjolein; van der Velpen, Isabelle; Mahfouz, Ahmed; van Roon-Mom, Willeke; Fedarko, Neal; Yasar, Sevil; Sabayan, Behnam; van Heemst, Diana; van der Weerd, Louise (Frontiers in Neuroscience, 2018)
Animal studies suggest the involvement of natriuretic peptides (NP) in several brain functions that are known to be disturbed during Alzheimer’s disease (AD). However, it remains unclear whether such findings extend to humans. In this study, we aimed to: 1) map the gene expression and localization of NP and their receptors (NPR) in human post-mortem brain tissue; 2) compare the relative amounts of NP and NPR between the brain tissue of AD patients and non-demented controls and 3) compare the relative amounts of NP between the cerebrospinal fluid (CSF) of AD patients and non-demented controls. Using the publicly available Allen Human Brain Atlas dataset, we mapped the gene expression of NP and NPR in healthy humans. Using immunohistochemistry, we visualized the localization of NP and NPR in the frontal cortex of AD patients (n=10, mean age 85.8 ± 6.2 years) and non-demented controls (mean age = 80.2 ± 9.1 years). Using Western blotting and ELISA, we quantified the relative amounts of NP and NPR in the brain tissue and CSF of these AD patients and non-demented controls. Our results showed that NP and NPR genes were ubiquitously expressed throughout the brain in healthy humans. NP and NPR were present in various cellular structures including in neurons, astrocyte-like structures, and cerebral vessels in both AD patients and non-demented controls. Furthermore, we found higher amounts of NPR type-A in the brain of AD patients (p=0.045) and lower amounts of NP type-B in the CSF of AD patients (p=0.029). In conclusion, this study shows the abundance of NP and NPR in the brain of humans suggesting involvement of NP in various brain functions. In addition, our findings suggest alterations of NP levels in the brain of AD patients. The role of NP in the development and progression of AD remains to be elucidated.